The art of computer virus research and defense - Szor, Peter (Addison-Wesley, 2005)
Symantec's chief antivirus researcher, Peter Szor, covers virus behavior and classification, protection strategies, antivirus and worm-blocking techniques, and more. Szor presents the state-of-the-art in malware and protection, providing the technical detail that professionals need to handle increasingly complex attacks. He provides information on code metamorphism and other emerging techniques, to anticipate and prepare for future threats.